Chromosome‐level genome assembly of the Arctic fox (Vulpes lagopus) using PacBio sequencing and Hi‐C technology. (21st April 2021) - Peng, Yongdong; Li, Hong; Liu, Zhengzhu; Zhang, Chuansheng; Li, Keqiang; Gong, Yuanfang; Geng, Liying; Su, Jingjing; Guan, Xuemin; Liu, Lei; Zhou, Ruihong; Zhao, Ziya; et al.
Abstract: The Arctic fox ( Vulpes lagopus ) is the only fox species occurring in the Arctic and has adapted to its extreme climatic conditions. Currently, the molecular basis of its adaptation to the extreme climate has not been characterized. Here, we applied PacBio sequencing and chromosome structure capture technique to assemble the first V . lagopus genome assembly, which is assembled into chromosome fragments. The genome assembly has a total length of 2.345 Gb with a contig N50 of 31.848 Mb and a scaffold N50 of 131.537 Mb, consisting of 25 pseudochromosomal scaffolds. The V . lagopus genome had approximately 32.33% repeat sequences. In total, 21, 278 protein‐coding genes were predicted, of which 99.14% were functionally annotated. Compared with 12 other mammals, V . lagopus was most closely related to V . Vulpes with an estimated divergence time of ~7.1 Ma. The expanded gene families and positively selected genes potentially play roles in the adaptation of V . lagopus to Arctic extreme environment. This high‐quality assembled genome will not only promote future studies of genetic diversity and evolution in foxes and other canids but also provide important resources for conservation of Arctic species.